PENGARUH TEKNIK MENGADUK ADONAN TERHADAP KUALITAS ROTI TAWAR - AD, Orin; Elida, Elida; Faridah, Anni (Faculty of Tourism and Hospitality - Universitas Negeri Padang, 2017)
This study aims to analyze the influence of dough mixing techniques on thequality of fresh bread which includes external quality and internal quality. Thistype of research is a true experiment conducted in August 2016 and located in theCulinary workshop. Types of data are primary data sourced from 5 expertpanelists by answering the organoleptic test format. Data were analyzed by usingindependent sample t test. The results showed that there were significant effects ofboth techniques, on the external quality of bread (volume, neat shape, rectangularshape 8 cmx 10 cm, and color), t count> t table. It means Ha accepted and on theinternal quality of fresh bread (texture, aroma, and taste) t arithmetic> t table.The best results based on the organoleptic test are found in X2 manual stirringtechnique because t count> t table (2.357, 2.546, 2.530, 3.286, 3, 536, 2. 887,3.647, 3.780, 4.333, 2.846, 2.357, 2.667> 2.30 ).Keywords: Mixing Technique, Quality, Fresh Bread